Patient-centered approach to pharmaceutical care in the recovery of patients with post-Covid syndrome - Petya Kasnakova; Stefka Ivanova (Pensoft Publishers, 2021)
The possibilities for pharmaceutical care in the recovery of patients with post-COVID syndrome in the context of a patient-centered approach have been explored. The global COVID-19 pandemic has necessitated a reorientation of the concept of providing healthcare to patients with COVID and post-COVID syndrome in patient-centered treatment and rehabilitation. Maximum recovery in holistic practice adopts a broader view of the patient's health, disease and treatment process. Applying a patient-centered approach to patients who have had a coronavirus infection will lead to many benefits, both in terms of the quality of health and pharmaceutical care, and in increasing their satisfaction with their quality of life.